Term Neonate with Atypical Hypoxic-Ischemic Encephalopathy Presentation: A Case Report - Townley, Nick; McNellis, Emily; Sampath, Venkatesh (American Journal of Perinatology Reports, 2017)
We describe a case of atypical hypoxic-ischemic encephalopathy (HIE) in a neonate following a normal pregnancy and delivery who was found to have an umbilical vein thrombosis. The infant arrived to our center with continuous bicycling movement of her lower extremities. She had a continuous electroencephalogram that showed burst suppression and magnetic resonance imaging of the brain showed diffusely abnormal cerebral cortical/subcortical diffusion restriction which may be secondary hypoxic-ischemic injury. Interestingly, a pathology report noted a focal umbilical vein thrombosis appearing to have compressed an umbilical artery with associated arterial dissection and hematoma. Our case illustrates how umbilical venous or arterial thrombosis may be associated with HIE and refractory seizures.
Keywords: Hypoxic-ischemic encephalopathy; umbilical vein thrombosis; status epilepticus